A Global Climatology of Tropopause Folds in CAMS and MERRA‐2 Reanalyses. Issue 8 (27th April 2021) - Akritidis, Dimitris; Pozzer, Andrea; Flemming, Johannes; Inness, Antje; Zanis, Prodromos
Abstract: Tropopause folds are the main mechanism underlying stratosphere‐to‐troposphere transport and influence tropospheric composition and weather systems by triggering convection. Here, we present the global climatology of tropopause folds in Copernicus Atmosphere Monitoring Service (CAMS) and Modern‐Era Retrospective analysis for Research and Applications, version 2 (MERRA‐2) reanalysis of atmospheric composition products for the time period from 2003 to 2018. We applied a 3‐D labeling algorithm in CAMS and MERRA‐2 reanalysis data to detect tropopause folding events. In constructing their climatologies, we show that the bulk of the folds are vertically shallow and are mainly found at the subtropical zones in the vicinity of the jet streams, while deeper folds also occur over the storm tracks, consistent with previous studies. The spatiotemporal characteristics of fold climatology are captured in a similar manner in CAMS and MERRA‐2, with MERRA‐2 capturing slightly higher frequencies during all seasons. In quantitative terms, there is a good agreement between CAMS and MERRA‐2 fold frequencies with spatiotemporal R 2 values of ∼0.9 for DJF, MAM, and JJA, and 0.75 for SON. The two reanalysis products are in close agreement regarding the intra‐ and interannual variability in fold frequency, with temporal correlation scores higher than 0.7 over the subtropical bands where the majority of folds are found. The agreement between the two reanalyses is lower in the Southern Hemisphere compared to the Northern Hemisphere. Thus, the global climatology of tropopause folds in both CAMS and MERRA‐2 reanalyses are similar to those of previous studies. Key Points: A 3‐D labeling algorithm is applied to detect tropopause folds in Copernicus Atmosphere Monitoring Service (CAMS) and Modern‐Era Retrospective analysis for Research and Applications, version 2 (MERRA‐2) reanalyses for the period 2003–2018 CAMS and MERRA‐2 fold climatologies are in line with previous studies, reproducing the key features of fold occurrence around the globe A good spatiotemporal agreement is found between CAMS and MERRA‐2 fold climatologies, which is more pronounced in the Northern Hemisphere